Hematological and blood biochemical variations, and their correlation with body condition in wild-foraging sea turtles of the Celebes Sea - Syamsyahidah Samsol,; Mohd Uzair Rusli,; Kirishnamoorthie Jeethvendra,; Nishizawa, Hideaki; Hussien Muin,; Juanita Joseph, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Celebes Sea provides critical foraging and migratory habitats for sea turtles in Malaysian waters, yet health status data, including hematologic and blood biochemistry parameters, remain scarce. To address this gap, we examined the blood profiles of green turtles and hawksbill turtles in these foraging grounds. Physical assessments such as body condition scores and indices suggested overall clinical health, though one green turtle exhibited fibropapillomatosis, and a new occurrence of the burrowing barnacle Chelolepas cheloniae was observed on the carapace. Blood samples from 32 green turtles and 4 hawksbill turtles were analyzed using an iSTAT handheld blood analyzer, showing interspecific differences in blood values. Hawksbill turtles exhibited higher blood urea nitrogen concentrations, possibly due to their high-protein diet, while one green turtle showed abnormal blood profiles indicative of potential acidosis. This study provides baseline health data for foraging sea turtles in the Celebes Sea, emphasizing the importance of hematological and biochemical monitoring in assessing health status and informing targeted conservation strategies to address threats in their foraging habitats. These findings help us better understand sea turtle health and support efforts to protect these important species and their habitats.